Engineered transgene integration platform (ETIP) for gene targeting and trait stacking - HENRY MATTHEW J; HAYDEN MATTHEW; MASON JOHN; SAWBRIDGE TIM; KUMAR SANDEEP; NOVAK STEPHEN; FORSTER JOHN; AINLEY W MIKE; COGAN NOEL; GUPTA MANJU; SPANGENBERG GERMAN; WEBB STEVEN R (2017)
An Engineered Transgene Integration Platform (ETIP) is described that can be inserted randomly or at targeted locations in plant genomes to facilitate rapid selection and detection of a GOI that is perfectly targeted (both the 5' and 3' ends) at the ETIP genomic location. One element in the subject disclosure is the introduction of specific double stranded breaks within the ETIP. In some embodiments, an ETIP is described using zinc finger nuclease binding sites, but may utilize other targeting technologies such as meganucleases, CRISPRs, TALs, or leucine zippers. Also described are compositions of, and methods for producing, transgenic plants wherein the donor or payload DNA expresses one or more products of an exogenous nucleic acid sequence (e.g. protein or RNA) that has been stably-integrated into an ETIP in a plant cell. In embodiments, the ETIP facilitates testing of gene candidates and plant expression vectors from ideation through Development phases. 本申请描述了用于基因打靶和性状堆叠的工程化转基因整合平台(ETIP)，它能在植物基因组中随机地或在靶定位